Optimalisasi Peran Kader Kesehatan Dalam Mencegah Stunting Melalui Pelatihan Penerapan Responsive Feeding Dan Pemenuhan Gizi Pada Bayi Balita Sesuai Panduan Buku KIA Di Puskesmas Karang Pule Kota Mataram - Ningsih, Mira Utami; Mas'adah, Mas'adah; Sulaeman, Ridawati (Universitas Mataram, 2024)
Stunting is still a public health problem, including in Mataram City, where the prevalence reaches 26.8%. The highest prevalence of stunting among 11 Health Centers in Mataram City is in the Karang Pule Health Center working area, which is 22.39%. Especially in Jempong Village, the percentage of stunted toddlers is 32%, with 22 children in West Jempong and 24 children in East Jempong. Something that is closely related to the incidence of stunting and stunted child development is the provision of nutrition from infants to toddlers. In this case, the role of parents, especially mothers in providing adequate nutritional intake for children, is very important. Mothers and health cadres complain about the difficulty of feeding children who have difficulty eating, who are picky eaters and only want to eat non-nutritious foods. Thus, the solution to the problem provided is to optimize the role of health cadres in fulfilling the nutritional needs of infants and toddlers for the prevention and treatment of stunting. This optimization activity is carried out by providing education to maternal and child health cadres to optimize the role of cadres in assisting mothers in meeting their children's nutritional needs.